Advancements in Electrochemical Biosensors for Comprehensive Glycosylation Assessment of Biotherapeutics - Preety Ahuja; Manpreet Singh; Sanjeev Kumar Ujjain (Sensors)
Proteins represent a significant portion of the global therapeutics market, surpassing hundreds of billions of dollars annually. Among the various post-translational modifications, glycosylation plays a crucial role in influencing protein structure, stability, and function. This modification is especially important in biotherapeutics, where the precise characterization of glycans is vital for ensuring product efficacy and safety. Although mass spectrometry-based techniques have become essential tools for glycomic analysis due to their high sensitivity and resolution, their complexity and lengthy processing times limit their practical application. In contrast, electrochemical methods provide a rapid, cost-effective, and sensitive alternative for glycosylation assessment, enabling the real-time analysis of glycan structures on biotherapeutic proteins. These electrochemical techniques, often used in conjunction with complementary methods, offer valuable insights into the glycosylation profiles of both isolated glycoproteins and intact cells. This review examines the latest advancements in electrochemical biosensors for glycosylation analysis, highlighting their potential in enhancing the characterization of biotherapeutics and advancing the field of precision medicine.